The Effect of Video Media Use on Increasing Students Knowledge and Attitudes Regarding The Smoke-Free Area Policy at MTs Waru Sukoharjo - Choirunnisa, Fadillah Zuhroh; Kusuma Estu Werdani (Universitas Muhammadiyah Surakarta, 2025)
The high prevalence of smoking in Indonesia, especially among adolescents aged 15 and above, remains a public health problem. Schools, as educational institutions, play a crucial role in shaping student behavior, including preventing smoking. This community service program aims to examine the impact of video-assisted education on students' knowledge and attitudes toward the Smoke-Free Area (KTR) policy at MTs Waru Sukoharjo. The study employed a quasi-experimental design with pre-test and post-test methods, and video as an intervention tool. Forty-five students participated in the study. The results, analyzed using the Wilcoxon test, showed a significant increase in students' knowledge (from a mean score of 5.40 to 6.11; p=0.002) and attitudes (from 10.06 to 11.60; p=0.004) after the education. These findings demonstrate that video media is effective in increasing students' awareness and support for the KTR policy at school. This initiative supports the broader goal of improving health and preventing early smoking among adolescents. The recommended follow-up is to monitor the implementation of policies in the school environment.